Risk of Subclinical Hypothyroidism in Breast Cancer Patients Treated With CT-Guided Radiation Therapy: A Prospective Observational Study - Amdisen L; Brink C; Lorenzen EL; Roenlev JD; Ewertz M; Cronin-Fenton D (Clinical Epidemiology)
Lau Amdisen,1 Carsten Brink,2,3 Ebbe Laugaard Lorenzen,2,3 Jeanette Dupont Roenlev,4 Marianne Ewertz,2 Deirdre Cronin-Fenton1 1Department of Clinical Epidemiology, Department of Clinical Medicine, Aarhus University and Aarhus University Hospital, Aarhus, Denmark; 2Department of Clinical Research, University of Southern Denmark, Odense, Denmark; 3Laboratory of Radiation Physics, Department of Oncology, Odense University Hospital, Odense, Denmark; 4Department of Oncology, Odense University Hospital, Odense, DenmarkCorrespondence: Lau Amdisen, Department of Clinical Epidemiology, Department of Clinical Medicine, Aarhus University and Aarhus University Hospital, Olof Palmes Allé 43-45, Aarhus N, 8200, Denmark, Tel +45 8716 8229, Email amdisen@clin.au.dkPurpose: The thyroid gland is an organ at risk in breast cancer survivors who receive radiation therapy to the supraclavicular lymph nodes. We investigated the effect of radiation dose to the thyroid gland on the incidence of hypothyroidism in early-stage breast cancer patients treated with CT-guided radiation therapy.Patients and Methods: We recruited women aged ≤ 75 years diagnosed with breast cancer from March 2016 through August 2017 at Odense University Hospital, Denmark. Thyroid function was measured in blood samples drawn at baseline, 6, 12, and 18 months. We delineated the thyroid gland using CT scans to estimate thyroid volume and radiation dose to the thyroid. Subclinical hypothyroidism was defined as a thyroid-stimulating hormone (TSH) level of > 4 milli-international units per liter (mIU/l) in the presence of normal free thyroxine. We also conducted a subanalysis with a threshold resulting in approximately 20% events within the cohort. We used mixed logistic regression to estimate associations between radiation dose to the thyroid and subclinical hypothyroidism.Results: Among 102 patients, four developed subclinical hypothyroidism. There was no association between increasing radiation dose to the thyroid and incidence of subclinical hypothyroidism. However, a trend was observed suggesting that higher mean radiation dose to the thyroid was associated with elevated risk of subclinical hypothyroidism at a TSH threshold of > 2.5mIU/l.Conclusion: Using current reference levels, increasing radiation dose to the thyroid was not associated with subclinical hypothyroidism, but at lower TSH thresholds, radiation therapy may predispose to hypothyroidism.Keywords: breast neoplasms, radiotherapy, hypothyroidism, thyroid gland